The Study of Learning Styles and its Relationship with Educational Achievement Among Iranian High School Students. (3rd August 2015) - Rezaeinejad, Maria; Azizifar, Akbar; Gowhary, Habib
Abstract: Learning process has been one of the important aspects of human life. Student's learning styles are among the acquired factors. Based on their individual differences, different students use different learning styles for their learning. The main purpose of this study was to investigate the study of learning styles among high school students and its relationship with educational achievement. The statistical population under investigation included girl's high school students in the city of Ilam, Iran in the school year of 2014. The statistical population was consisted of 3958 students. The sample group was selected by the stratified random sampling method based on Morgan's table and through multiple-steps sampling. In order to assess the learning styles, the online questionnaire for learning styles, by Felder and Solomon is used. Collected data analyzed using SPSS software. According to correlation coefficients, among students in experiential field, there is a positive significant relationship between students learning styles who use Visual-Verbal learning style and their score means and among students in mathematics field, there is a positive significant relationship between students learning styles who use Active-Reflective and Visual-Verbal learning style and their score mean. In humanities field, there is no significant relationship between the students learning styles that use Sequential-Global, Visual-Verbal and Sensing- Intuitive learning styles and their score means. The Kruskal-Wallis test shown that there is a significant difference between humanities students score means with mathematics and experiential students that have Active-Reflective learning style. There is a significant difference between score means of grade two students in all fields in Active-Reflective and Visual-Verbal learning styles and similarly in grade three students in all fields in Active-Reflective and Sequential-Global learning styles.